Analyzing the Effects of Policy Reforms on the Poor : An Evaluation of the Effectiveness of World Bank Support to Poverty and Social Impact Analyses - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The current global financial and economic crises are likely to put enormous pressure on governments to respond with immediate measures and to undertake far-reaching reforms in the medium term, requiring a substantial increase in donor support. To protect the poor and enhance benefits to them, key policy reforms will need to be underpinned by systematic analysis of their expected poverty and social impacts. The World Bank's experience to date with the Poverty and Social Impact Analysis (PSIA) approach provides useful lessons for addressing these issues. Overall, implementation of the PSIA approach has had considerable limitations. There have been tensions between the various operational objectives assigned to PSIAs. The tensions concern inconsistencies between informing country and Bank policy decisions in a timely way and building country analytic capacity. PSIAs have had limited ownership by Bank staff and managers and have often not been effectively integrated into country assistance programs. Quality assurance, monitoring, and evaluation of the overall effectiveness of PSIAs have been weak. To improve PSIAs' effectiveness, this evaluation recommends that the Bank take measures to ensure that staff fully understands what the PSIA approach is and when to use it, clarify the operational objectives of each PSIA, and ensure that the approach and timeline adopted are aligned with those objectives. Quality assurance mechanisms should be strengthened to ensure that PSIAs are designed to achieve the intended effects.